2016
DOI: 10.1111/ijn.12431
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for implementing genomics into nursing practice informed by three behaviour change theories

Abstract: Genomics is an ever increasing aspect of nursing practice, with focus being directed towards improving health. The authors present an implementation strategy for the incorporation of genomics into nursing practice within the UK, based on three behaviour change theories and the identification of individuals who are likely to provide support for change. Individuals identified as Opinion Leaders and Adopters of genomics illustrate how changes in behaviour might occur among the nursing profession. The core philoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The education challenges presented here resonate with those identified in the literature. The engagement of nursing leadership is vital to establishing genomics competency as a workforce priority (Calzone et al., in press; Jenkins et al., ; Leach, Tonkin, Lancastle, & Kirk, ). To achieve engagement, relevancy of genomics must be established, which requires that nursing leaders attain competency in genomics sufficient to inform their decisions on competency standards and infrastructure priorities, such as point of care decision supports (Jenkins et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The education challenges presented here resonate with those identified in the literature. The engagement of nursing leadership is vital to establishing genomics competency as a workforce priority (Calzone et al., in press; Jenkins et al., ; Leach, Tonkin, Lancastle, & Kirk, ). To achieve engagement, relevancy of genomics must be established, which requires that nursing leaders attain competency in genomics sufficient to inform their decisions on competency standards and infrastructure priorities, such as point of care decision supports (Jenkins et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Rogers’ Diffusion of Innovations () documents that this complexity and lack of observability all slow adoption. Policy approaches, the involvement of critical healthcare leaders, and the utilization of opinion leaders, such as the G2NA delegates, can help facilitate adoption (Leach et al., ). But those G2NA country delegates alone will not be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…It is time to move beyond justifying the relevance of genomics in nursing practice (Leach, Tonkin, Lancastle, & Kirk, ). Therefore, the aim of this study is not to justify the importance of genomics in nursing practice.…”
mentioning
confidence: 99%
“…They identified 10 CFIR constructs as high priority. In nursing and genomics, behavior change theories have played an important role in implementation studies (Leach, Tonkin, Lancastle, & Kirk, 2016), with Diffusion of Innovations being perhaps the most widely used, such as in a large‐scale U.S. program (Jenkins et al, 2015). Williams et al (2017) identified three key areas for nurses at the IS–genomics intersection (nurse leadership, genomics literacy, and learning from change) to understand the determinants of successful and failed implementation.…”
Section: Introductionmentioning
confidence: 99%